2018
DOI: 10.1038/s41598-018-33969-9
|View full text |Cite
|
Sign up to set email alerts
|

Bispectrum Features and Multilayer Perceptron Classifier to Enhance Seizure Prediction

Abstract: The ability to accurately forecast seizures could significantly improve the quality of life of patients with drug-refractory epilepsy. Prediction capabilities rely on the adequate identification of seizure activity precursors from electroencephalography recordings. Although a long list of features has been proposed, none of these is able to independently characterize the brain states during transition to a seizure. This work assessed the feasibility of using the bispectrum, an advanced signal processing techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 20 publications
0
23
0
1
Order By: Relevance
“…The preictal part consisted of a 5-minute section one hour before the seizure onset, and the interictal state consisted of a 5-minute section four hours away from the seizure. The authors used 30-sec non-overlapping segments for feature extraction and reported that the best testing accuracy obtained for preictal and interictal classification was 78.11% [40].…”
Section: Discussionmentioning
confidence: 99%
“…The preictal part consisted of a 5-minute section one hour before the seizure onset, and the interictal state consisted of a 5-minute section four hours away from the seizure. The authors used 30-sec non-overlapping segments for feature extraction and reported that the best testing accuracy obtained for preictal and interictal classification was 78.11% [40].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed that extracting features from different domains, including time domain, frequency domain, and/or time-frequency domain, is effective for developing epileptic seizure detection models [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 23 , 24 , 25 , 26 ]. Although these three types of features were proposed, none are able to comprehensively characterize EEG signals.…”
Section: Methodsmentioning
confidence: 99%
“…In frequency domain analysis, the main methods include fast Fourier transform [ 15 ], higher-order spectra [ 16 ], bispectrum [ 17 , 18 ], power spectral analysis [ 19 ], eigenvectors [ 20 ], etc. Polat and Günes extracted the relevant features from raw EEG signals using fast Fourier transform, and built a hybrid system to detect epileptic seizures [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prompts us to study the interaction between frequencies of the EEG signal to track the changes in EEG arising from linear and nonlinear changes under a variety of physiologic conditions. Recently, the higher-order statistic (HOS) methods [16][17][18][19][20][21] such as bispectrum (BS) and wavelet bispectrum (WBS) have been used for extracting features of the bio-signals. HOS methods explore the existence of quadratic (and cubic) nonlinear coupling between the different frequency components of a signal.…”
Section: Introductionmentioning
confidence: 99%